Streptococcus pneumoniae as a Cause of Salpingitis - David Patterson; Celeste M. Johnson; Gilles R. G. Monif (Hindawi Limited, 1994)
Background: A case of pneumococcal septicemia associated with laparoscopically documented acute salpingitis is reported.